Tissue cytokines in chickens from lines selected for high or low humoral antibody responses, given supplemental Limosilactobacillus reuteri and challenged with Histomonas meleagridis - Edens, Frank W.; Siegel, Paul B.; Beckstead, Robert B.; Honaker, Christa F.; Hodgson, Dellila (Frontiers in Physiology, 2024)
Histomonas meleagridis, a protozoan parasite, induces blackhead disease (histomoniasis) in poultry. At hatch, chicks from lines divergently selected for high (HAS) and low (LAS) antibody response to sheep red blood cells were divided into two groups each of HAS and LAS and placed in pens with wood shavings as litter. Feed and water were allowed ad libitum. Half of the chicks from each line had Limosilactobacillus reuteri (L. reuteri) added to their drinking water. At d 18, all chicks were given a transcloacal inoculation of 100,000 H. meleagridis cells. Ten days later, they were euthanized followed by collection of tissues from brain, cecal tonsil, ceca, liver, thymus, and spleen for qPCR analyses of cytokines involved in immunological development.Changes in cytokine expressions were most numerous in the cecal tonsil, ceca, and liver. In the absence of a functional medication for control of histomoniasis, L. reuteri and/or its secretory product, reuterin might serve, in some genetic populations, as a means to reduce the impact of histomoniasis in chickens. The data demonstrate that L. reuteri treatment had tissue specificity between the two genetic lines in which the effects were targeted primarily toward the cecal tonsil, ceca, and liver, primary tissue targets of the parasite (Histomonas meleagridis), as well as the thymus and spleen. However, interactions among main effects reflect that responses to inflammatory markers observed in tissues for one genetic line may not be observed in another.